Experimenting with Wellbeing: Basic Income, Immaterial Labour and Changing Forms of Productivity - Adkins Lisa; Ylöstalo Hanna (SAGE PUBLICATIONS INC, 2025)
This article is concerned with the recent (2017-2018) basic income experiment in Finland. This experiment attracted global attention, not least because of its break from the conditionalities and sanctions associated with social security payments in workfare states. This article stresses, however, that it is critical to understand how the Finnish basic income experiment was part of a broader programme of government-led reform in Finland. As well as establishing the experiment as a preferred mode of policymaking, this programme contained a range of strategies aimed at restructuring labour supply. The article shows how the basic income experiment should be understood as a behavioural intervention designed to enhance the wellbeing of unemployed populations at a time when wellbeing is emerging as a value-producing capacity.